Personalización del Moodle mediante la integración de las tecnologías educativas de la web más empleadas en la educación superior (2019)
The purpose of the research was to integrate Moodle with the tools of the web 2.0 most used in the teaching learning processes jointly. Anki, Cmap, Etherpad, Facebook, Google Scholar, Kahoot, Skype, Simple Solver, Twitter, Wolfram Alpha, Wordsift and YouTube were selected for their educational approach, interdisciplinary and ease of use. It was analyzed the kinds of extensions that can be developed for Moodle and its functionalities and it was determined that the block extension is the appropriate one to integrate Moodle with several technologies at the same time. The block was implemented in the PHP programming language. The plugin “Web Technologies” creates a technological environment focused on the student and guided by the teacher. It incorporates all the tools, contents and people involved in the digital part of the educational process. It also converts Moodle into a Personal learning environment.